Aplicação de um secador convectivo assistido por aquecimento infravermelho para a secagem de sementes de maracujá-amarelo - Batista, Ageu Ícaro da Silva (2021)
Passion fruits seeds, residues from processing industries to produce juice and frozen pulp are a valuable feedstock to be re-used as for specie propagation or as non-conventional source of oil, carbohydrates, proteins and minerals. Because of the great amounts of seeds in these residues, add value to this co-product is of economical, scientific and technological interest. Drying is one of the more traditional conservation methods for processing and preserving seeds. However, the convective drying technique has as main problem the high energy consumption. Thus, in order to optimize the thermal conditions and reduce the energy cost of the process, in this work a hybrid dryer based on the simultaneous hot air convection and infrared (IR) heating was developed, with on line monitoring and acquisition of air temperature, IR source temperature, seed temperature and loss of moisture from the sample. Experiments were performed with IR source temperatures of 50, 65 and 80°C, air temperatures of 30, 40 and 50°C, and air velocities of 1, 2 and 3 m/s. To describe the drying kinetics the diffusion model was fitted to the experimental data. The effects of process variables on the effective moisture diffusivity in passion fruit seeds and specific energy consumption (SEC) were examined. In combined drying the air and IR source temperatures affected significantly draying rates and decreased the process time in comparison to the convective drying. The maximum effective diffusivity (1,06 x 10-10 m2 /s) was observed t TIV = 80°C, Tar = 50oC and var = 2 m/s, while the mínimum SEC has occurred at TIV = 80°C, Tar = 30oC and var = 1 m/s. The incorporation of IR heating to the hot air convection intensified mass transfer and decreased the specific energy consumption of the process, ensuring preservation of physiological quality of the product, being suggested as optimal condition the combination of the highest IR source temperature with the lowest air temperature.